Effects of orthodontic forces on dental pulp : A summary of recent data - Huokuna, Jukka (My University, 2020)
The aim of this review is to provide a summary of recent data on the effects of orthodontic treatment on dental pulp. Articles published between February 2009 and July 2020 were searched electronically on the PubMed database, and 27 relevant articles were identified. Orthodontic force appears to cause a reduction in pulpal blood flow and in the tooth’s sensitivity to electric pulp testing. In addition, there were indications of increases in the expression or activity levels of enzymes and neuropeptides associated with metabolic changes and inflammation (aspartate aminotransferase (AST), the neuropeptides calcitonin gene-related peptide (CGRP) and substance P (SP), inducible nitric oxide synthase (iNOS) and matrix metalloproteinases (MMPs)). Most commonly reported histological changes in the pulp were vacuolization and disruption of the odontoblastic layer as well as vascular changes. The observed changes in the pulp were in most cases only temporary, appearing within days of initiating the treatment and usually lasting for weeks. There were no clear signs of permanent damage.

Tämän kirjallisuuskatsauksen tavoitteena on tarkastella uusinta tietoa oikomishoidossa käytettävien voimien vaikutuksista hampaan ytimeen. Julkaisuja haettiin sähköisesti PubMed tietokannasta ajanjaksolta helmikuun 2009 ja heinäkuun 2020 välillä. Katsaukseen hyväksyttiin 27 kriteerit täyttävää julkaisua. Julkaisujen perusteella oikomishoidossa käytettävä voima näyttäisi väliaikaisesti vähentävän hammasytimen verenkiertoa sekä alentavan sen herkkyyttä sähköisessä herkkyysmittauksessa. Lisäksi ilmi tuli viitteitä siitä, että useilla metabolisiin muutoksiin ja tulehdusmuutoksiin liittyvillä entsyymeillä ja neuropeptideillä olisi kohonnut aktiivisuus tai ilmentyminen oikomalla siirretyn hampaan ytimessä. Useimmin raportoidut histologiset löydökset hammasytimessä olivat vakuolisaatio, odontoblastikerroksen rikkonaisuus sekä verisuonimuutokset. Hammasytimessä havaitut muutokset olivat luonteeltaan enimmäkseen väliaikaisia. Muutokset ilmenivät useimmiten päivien sisällä voiman asettamisesta ja kestivät tyypillisesti viikkojen ajan. Kirjallisuuskatsaukseen otettujen julkaisujen perusteella oikomishoidossa käytettävät voimat eivät näyttäisi aiheuttavan pysyviä muutoksia hampaan ytimeen.
Keywords: hammasydin, hampaan herkkyysmittaus, hampaan verenkierto, oikomishoito